PERENCANAAN PENDIDIKAN DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 1 REMBANG - Pujoko; Ana Supriati; Sudadi; Nuraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze school program planning to improve the quality of education at SMP Negeri 1 Rembang. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observation and documentation. Informants consisted of school principals, teachers, students and parents. Data analysis was carried out descriptively using data reduction techniques, data presentation and drawing conclusions. The research results showed that program planning in schools was carried out through program preparation referring to education report cards. The main obstacles faced are the high expectations of the school community regarding school programs, the lack of awareness of several parties regarding the programs being held, and inadequate reflection on finances. The way to overcome obstacles based on education report cards is by identifying, reflecting and improving and evaluating with the team, fixing everything that is lacking in planning and implementation and then applying the results of the evaluation/reflection in activities. This research suggests that when preparing a school program, the principal should consider everything so that the program being prepared can meet the needs of the school community.